Green, circular, and digital economies as tools for recovery and sustainability - Ordóñez de Pablos, Patricia, 1975-; Zhang, Xi (Researcher in business management), 1982-; Almunawar, Mohammad Nabil, 1960- (Business Science Reference, an imprint of IGI Global, 2022)
"The book explores new and emerging frameworks, tools, strategies to support companies and economies towards the green and digital transformation in Asia, with special focus on ASEAN by analyzing the role of disruptive technologies, cutting-edge green technologies and in these emerging practices in Asia and how they can boost the creation of new business opportunities, more jobs and economic growth for the recovery of Asian economies in post-covid-19 scenarios"--